Bacillus anthracis Bioterrorism Incident, Kameido, Tokyo, 1993 - Hiroshi Takahashi; Paul Keim; Arnold F. Kaufmann; Christine Keys; Kimothy L. Smith; Kiyosu Taniguchi; Sakae Inouye; Takeshi Kurata (Emerging Infectious Diseases, 2004)
In July 1993, a liquid suspension of Bacillus anthracis was aerosolized from the roof of an eight-story building in Kameido, Tokyo, Japan, by the religious group Aum Shinrikyo. During 1999 to 2001, microbiologic tests were conducted on a liquid environmental sample originally collected during the 1993 incident. Nonencapsulated isolates of B. anthracis were cultured from the liquid. Multiple-locus, variable-number tandem repeat analysis found all isolates to be identical to a strain used in Japan to vaccinate animals against anthrax, which was consistent with the Aum Shinrikyo members’ testimony about the strain source. In 1999, a retrospective case-detection survey was conducted to identify potential human anthrax cases associated with the incident, but none were found. The use of an attenuated B. anthracis strain, low spore concentrations, ineffective dispersal, a clogged spray device, and inactivation of the spores by sunlight are all likely contributing factors to the lack of human cases.